Impact of Air Pollution on Human Health in India - Dr. Sanjay Shahi (International Journal of Engineering and Management Research, 2020)
Natural and artificial environmental factors have combined to produce poor air quality in the majority of the world's megacities. Development countries face an even more acute and intricate problem with pollution in the air than industrialized nations. Emissions and trans boundary movement of air pollutants are two possible sources of control for pollution levels in the atmosphere. Each factor enters the atmosphere in a different way and has a varied effect on the environment. The issue that needs to be dealt with is figuring out how and where emissions come from. Air pollution is an important issue, but it's even more difficult to investigate and solve the patterns or chemistry of the most prevalent air pollutants. It is critical to locate the primary sources of air pollutants since secondary air pollutants can only be generated by these sources. Primary air pollutants, their nature, emission budgets, and their influence on environmental and human health are discussed in detail in this review, which aims to shed light on the basic principles of air pollution. In the end, some of the policies and regulations to reduce primary air pollutants are discussed.